American folk masters the National Heritage Fellows - Siporin, Steve (Harry N. Abrams, Inc., a Times Mirror Company, 1992)
American Folk Masters celebrates the lives and work of nearly 150 National Heritage Fellows, named since 1982 as exemplary practitioners of traditional folk arts. Sometimes likened to Japan's Living National Treasures, the Fellows are selected each year by the Folk Arts Program of the National Endowment for the Arts for their achievements in a wide variety of visual and performing folk arts. The National Heritage Fellows come from Maine and Hawaii, from Alaska and Puerto Rico, and from most states in between. A random roll call of even a few of their names - Duff Severe, Periklis Halkias, Canray Fontenot, Alice New Holy Blue Legs - reflects America's rich ethnic diversity. And the same diversity characterizes the arts the Fellows practice, which range from blues music, pottery, tap dancing, and lace making to Lakota quillwork, Sicilian marionette theater, African-American story-telling, and Hawaiian quiltmaking. Published on the tenth anniversary of the National Heritage Fellowships, this volume was inspired by an exhibition organized by the Museum of International Folk Art in Santa Fe. Its fifty full-page color photographs show the compelling, beautifully crafted objects made by the visual artists among the Fellows, while its black-and-white portraits and personal quotations capture the fascinating backgrounds and personalities of these people. Steve Siporin, folklorist and Associate Professor at Utah State University, has written a lively yet thoughtful essay that considers the Fellows as inheritors, innovators, and conservers of tradition. There are contributions by Bess Lomax Hawes, Director of the Folk Arts Program of the National Endowment for the Arts (1977-92), and Barre Toelken, Professor of Folklore at Utah State University. A comprehensive illustrated Directory of all the Fellows from the last ten years includes an invaluable bibliography, discography and filmography. The first full-length study of a groundbreaking program, American Folk Masters has much to offer anyone who values our national heritage. Whether descendants of the original Native peoples or members of the newest immigrant group, we can all learn from these consummate artists who are keeping our folk traditions alive today.